Implementasi Penerbitan Sertifikat Produksi Pangan Industri Rumah Tangga Di Provinsi Gorontalo - Retno Anggrina Khalistha Dewi; Cakra Asrial; Winiati P. Rahayu (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2020)
Every human being has the right to obtain safe and quality food, include food from household industry (industri rumah tangga pangan/IRTP). The objective of this research is to determine the implementation of BPOM Regulation Number 22 year 2018 related to the issuanced of food production certificate of household industries (SPP-IRT) by the district health office (DHO) and the district office of one stop integrated investment service (OSIIS). The study was taked from six districts area in Gorontalo. The result showed that three (50%) DHOs included in the group I (obedient), and one DHO each classified into group II (quite obedient), III (somewhat obedient), and IV (less obidient). Three OSHSs issued SPP-IRT with recommendation by DHO and used online single submission (OSS) as application for issuing SPP-IRT certificate.